2015
DOI: 10.1038/srep13439
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Clinicopathology of Early Gastric Carcinoma between Proximal and Distal Location in 438 Chinese Patients

Abstract: Early gastric carcinoma (EGC) in Chinese patients remains poorly understood and endoscopic therapy has not been well established. Here, we compared endoscopic and clinicopathologic features between early proximal gastric carcinoma (PGC, n = 131) and distal gastric carcinoma (DGC, n = 307) in consecutive 438 EGCs diagnosed with the WHO criteria. By endoscopy, PGCs showed protruding and elevated patterns in 61.9%, while depressed and excavated patterns in 33.6%, which were significantly different from those (32.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
97
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 73 publications
(143 citation statements)
references
References 39 publications
42
97
3
Order By: Relevance
“…More recently, Lee et al [26] reported a high (18.3%, 9/49) frequency of lymph node metastasis in early papillary adenocarcinoma of Korean patients. The abovementioned results have been confirmed most recently in Chinese patients [14,18]. Compared to early tubular adenocarcinoma, early papillary adenocarcinoma is associated with a significantly worse 5-year survival rate (80.5% compared to 96.8% in early tubular adenocarcinoma, p < 0.05), significantly more submucosal invasion (64.4 vs. 43.6%) ( p < 0.05), and the micropapillary growth pattern (6.8 vs. 0%) ( p < 0.003) [18].…”
Section: Worse Prognosis For Early Papillary Adenocarcinomasupporting
confidence: 62%
See 4 more Smart Citations
“…More recently, Lee et al [26] reported a high (18.3%, 9/49) frequency of lymph node metastasis in early papillary adenocarcinoma of Korean patients. The abovementioned results have been confirmed most recently in Chinese patients [14,18]. Compared to early tubular adenocarcinoma, early papillary adenocarcinoma is associated with a significantly worse 5-year survival rate (80.5% compared to 96.8% in early tubular adenocarcinoma, p < 0.05), significantly more submucosal invasion (64.4 vs. 43.6%) ( p < 0.05), and the micropapillary growth pattern (6.8 vs. 0%) ( p < 0.003) [18].…”
Section: Worse Prognosis For Early Papillary Adenocarcinomasupporting
confidence: 62%
“…Compared to distal carcinomas, small proximal gastric carcinomas feature a significantly higher male-to-female ratio (3.1 vs. 1.7, p < 0.05), older mean age (63 years vs. 59, p < 0.05), and the absence of patients younger than 40 years [13]. Similar characteristics have been found in EGCs of the same patient population [14]. The results provide the pathologic evidence on possible Lgr5 + stem cell-driven tumorigenesis mechanism in those 2 areas.…”
Section: Gastric Regions At High Risk For Early Carcinomasupporting
confidence: 59%
See 3 more Smart Citations